Chlorogenic Acid as a Positive Regulator in LPS-PG-Induced Inflammation via TLR4/MyD88-Mediated NF-κB and PI3K/MAPK Signaling Cascades in Human Gingival Fibroblasts - Park, Chung Mu; Yoon, Hyun-Seo (Mediators of Inflammation, 2022)
Gingival inflammation is one of the main causes that can be related to various periodontal diseases. Human gingival fibroblast (HGF) is the major constituent in periodontal connective tissue and secretes various inflammatory mediators, such as nitric oxide (NO) and prostaglandin E2 (PGE2), upon lipopolysaccharide stimulation. This study is aimed at investigating the anti-inflammatory mechanism of chlorogenic acid (CGA) on Porphyromonas gingivalis LPS- (LPS-PG-) stimulated HGF-1 cells. The concentration of NO and PGE2, as well as their responsible enzymes, inducible NO synthase (iNOS), and cyclooxygenase-2 (COX-2), was analyzed by Griess reaction, ELISA, and western blot analysis. LPS-PG sharply elevated the production and protein expression of inflammatory mediators, which were significantly attenuated by CGA treatment in a dose-dependent manner. CGA treatment also suppressed activation of Toll-like receptor 4 (TLR4)/myeloid differentiation primary response gene 88 (MyD88) and nuclear factor- (NF-) κB in LPS-PG-stimulated HGF-1 cells. Furthermore, LPS-PG-induced phosphorylation of extracellular regulated kinase (ERK) and Akt was abolished by CGA treatment, while c-Jun N-terminal kinase (JNK) and p38 did not have any effect. Consequently, these results suggest that CGA ameliorates LPS-PG-induced inflammatory responses by attenuating TLR4/MyD88-mediated NF-κB, phosphoinositide-3-kinase (PI3K)/Akt, and MAPK signaling pathways in HGF-1 cells.